Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
4 Answers
- ShadowLv 410 years ago
Differentiating it, you get:
3x^2 + 3/2
Sub in x=1, the gradient at point (1,2) is:
3 + 3/2 = 9/2
Using Y = mX + c, sub in Y=2, m=9/2, X=1:
2 = 9/2 * 1 + c
c = -5/2
Hence the equation of the tangent line is:
y = 9/2 x - 5/2
OR
2y = 9x - 5
- Anonymous10 years ago
The point (1, 2) is invalid.
I don't know if you meant y = x^3 + (3/2)x or y = x^3 + 3/(2x), but either way, if you substitute x = 1 and y = 2, the equation is false.
- TheSicilianSageLv 710 years ago
Please watch your parentheses.
You must mean:
... y = (x^3 + 3) / (2x)
or dy/dx = x - 3/(2x^2) [ @ x = 1 ] = -.5 ← slope
... y = mx + b
or y = -.5x + b
or 2 = -.5(1) + b
or b = 2.5
... y = -.5x + 2.5 ← final answer in slope-intercept form
- 10 years ago
y=x^3+3/2x
y'=3x^2+3/2
3x^2=-3/2
x^2=-1/2
x=-sqrt(1/2)
y-2=-sqrt(1/2)*(x-1)
y=2-sqrt(1/2)*(x-1)